A Specific Photoreaction in Polydeoxyadenylic Acid - Pörschke, Dietmar (1973)
Ultraviolet photosensitivity of the single-stranded forms of poly(A) and poly(dA) is compared. In contrast to poly(A), poly(dA) is rather sensitive to ultraviolet irradiation. Relatively low doses of ultraviolet light lead to characteristic changes of the ultraviolet and circular dichroism spectra of poly(dA), suggesting formation of a specific photoproduct in poly(dA) that cannot be formed in poly(A). The quantum yields in poly(dA) (ϕ = 2.5 × 10(-3)) are about a factor of 10 higher than in poly(A), indicating a high structure specificity. The base-pairing capacity of irradiated probes of poly(dA) to poly(dT) is inhibited. These results demonstrate a relatively high probability of DNA photolesions, that cannot be repaired by simple repair enzyme systems.